Identification of the Direction and Strength of Relationship between Complaints of Musculoskeletal Disorders (MSDs) to Smoking Habits and Repetitive Movements of Informal Workers in Surabaya, Indonesia Using Spearman Correlation Test Methods (Indian Journal of Forensic Medicine & Toxicology, 2020)
The right statistical test to find out the relationship between variables that have ordinal data scale is aspearman correlation test. Spearman correlation shows how strong the relationship and the direction of therelationship between variables. The increasing muscle complaints have a close relationship with smokinghabits. The longer and the higher the frequency of people smoke, the smaller the lung capacity. It thenresults in a decrease in the lung ability to consume oxygen. It also causes one more easily tired whencarrying out tasks that require exertion. In addition, complaints due to repetitive movements occur becausethe muscles continuously receive workload pressure without a chance for relaxation. This condition triggersthe occurrence of nerve swelling which will cause pain in the musculoskeletal area. This is an observationalstudy with a cross sectional design. The study used a total sampling population of 12 workers. Spearmancorrelation is used to examine the strength and direction of the relationship between the dependent variable,MSDs complaints, an ordinal data scale, with independent variables, smoking habits and repetitivemovements. This study found that smoking habits and the level of complaints of MSDs in the shelf framebending workers have fairly strong, positive and unidirectional relationship with correlation coefficientvalue of 0.357. It also found that repetitive movements and complaint levels MSDs have a positive andperfect relationship with the correlation coefficient value of 1,000.